ESSAY FOR THE CONTEMPORARY PATRIOTS IN MACEDONIA IN 2016! - Ana Ashtalkovska Gajtanoska (EtnoAntropoZum, 2018)
This note about the patriots in Macedonia in 2016 is referring to the political (miss)use of this term in contemporary situation marked by the protests that began on 12.04.2016. Two groups of Macedonian citizens protest thorough the streets in Macedonia – one group protests “against the regime” of the government, and the other group protests for “defending Macedonia” and the current government. The two groups, among other things disagree on the question of what the term patriotism represents to them and it seems that it is about completely different concepts on the relation of the individual towards one’s own state and the relation of the “people” towards the state (and vice versa). The second conception about patriotism is especially interesting and is regularly used by the “Civil Movement for Defense of Macedonia” and their rhetoric is very much alike the one that has been used in 19 centuries in the phases of nation building particularly in Southeast Europe. In that sense what is interesting is how this 19 century concept is still so popular in Macedonia in the 21 century!